Menghitung frekuensi respirasi, denyut nadi dan tekanan darah - Anwar, Hanum Salsabila (Maliki Interdisciplinary Journal, 2025)
This research discusses the human respiratory system which consists of a series of organs and tissues that function to exchange gases, take in oxygen from the atmosphere and remove carbon dioxide. The respiration process begins with the entry of air through the nose or mouth, which then passes through the respiratory tract until it reaches the lungs, where oxygen is absorbed by the blood through the alveoli and carbon dioxide is expelled. Apart from providing oxygen for cellular metabolism, this system also plays a role in maintaining acid-base balance and protecting the body from foreign particles. Organs such as the nose, throat, larynx, trachea, and lungs work synergistically to ensure efficient gas exchange. The respiration process affects pulse rate and blood pressure, with increased oxygen flow which can increase pulse rate due to increased metabolism. Various factors such as exercise, acute pain, anxiety, and body position affect the frequency and depth of breathing. This research emphasizes the importance of the respiratory system in maintaining the health and physiological balance of the human body, reflecting the complex integration between systems that also has a spiritual dimension.